Beginning Windows 8 Data Development Using C# and JavaScript - Kumar, Vinodh. (Apress : Imprint: Apress, 2013)
This book introduces novice developers to a range of data access strategies for storing and retreiving data both locally and remotely. It provides you with a range of fully working data access solutions and the insight you need to know when, and how, to apply each of the techniques to best advantage. Focussing specifically on how the Windows 8 app developer can work with the Windows Runtime (often called Windows RT) framework this book provides careful analysis of the many options you have open to you, along with a comparision of their strengths and weaknesses under different conditions. With the days of a single database being the right choice for almost all development projects long gone. You will lean that the right choice for your app now depends on a variety of factors and getting it right will be critical to your customer's end user experience. We cover a range of data access strategies ranging from storing and retrieving data locally using the JET API, to using the most popular open and closed source database products like SQLite and SQL Server. We look at how lightweight HTML and JavaScript apps work well with equally feather-weight data stores like IndexedDB. We'll also introduce you to more advanced data access techniques like REST (JSON), WCF RIA Services, ASP.NET MVC 4 Web API and Windows Azure that can hugely expand the horizons of what it is possible for your app to do as storage - and even processing - are taken beyond the confines of your user's device. By the time you have read this book you will be familiar with the key data access considerations you will need to evaluate as you build you apps and you will be able to confidently select the data access architecture that is most appropriate to the app you want to build.